Architectural and Structural Analysis of the Tamang Houses in Haku, Rasuwa - Häberle, Jonas Raphael; Shrestha, Jagat Kumar (Journal of the Institute of Engineering, 2020)
This paper provides a summary of an architectural and structural analysis of traditional Tamang houses in Haku, Rasuwa and the best methods for integrating seismic resistant features and cultural preservation in the recovery after the 2015 Nepal earthquakes.